Pathways for sediment transport and retention in a vegetated, mid‐channel island: Connecting sediment dynamics to morphology in Meinmahla Island, Ayeyarwady Delta, Myanmar. Issue 1 (5th October 2022) - Glover, Hannah E.; Ogston, Andrea S.; Fricke, Aaron T.; Nittrouer, Chuck A.; Aung, Cherry; Naing, Thet; Lahr, Evan J.
Abstract: Vegetated mid‐channel islands play an important though poorly understood role in the sediment dynamics and morphology of tide‐dominated deltas. Meinmahla Island is a mangrove‐forest preserve at the mouth of the Bogale distributary channel, in the Ayeyarwady Delta, Myanmar. In this relatively unaltered mid‐channel island, sediment dynamics can be directly connected to morphology. Field measurements from 2017 to 2019 provide insight into the pathways for sediment transport and resulting morphological evolution. Water depth, salinity and turbidity were monitored semi‐continuously, and velocity profilers with turbidity and salinity sensors were deployed seasonally in single‐entrance (dead‐end/blind) and multi‐entrance tidal channels of the island. The morphological evolution was evaluated using grain size, 210 Pb geochronology, remote sensing and channel surveys. The data show that ebb‐dominant, single‐entrance channels along the island exterior import sediment year‐round to the land surface. However, these exterior channels do not deliver enough sediment to maintain the observed ca 0.8 cm/yr accretion rate, and most of the sediment import occurs via interior, multi‐entrance channels. Interior channels retain water masses that are physically distinct from the water in the Bogale distributary, and estuarine processes at the tidal‐channel mouths import sediment into the island. Sediment is sourced to the island from upriver in the wet season and from the Gulf of Mottoma in the dry season, as the location of the estuary shifts seasonally within the Bogale distributary. The salinity and biogeochemistry of the distributary water are affected by interactions with sediment and groundwater in the island interior. The largest interior channels have remained remarkably stable while the island has aggraded and prograded over decadal timescales. However, the studied multi‐entrance channel is responding to a drainage‐network change by narrowing and shoaling. Overall, mid‐channel islands trap sediment and associated nutrients at the river–ocean interface, and these resilient landscape features evolve in response to changes in drainage‐network connectivity.